2017
DOI: 10.1038/ijo.2017.274
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of mitochondrial function and biogenesis modulators in adipose tissue of obese children

Abstract: Adipose tissue from children with obesity demonstrates a dysregulation of key modulators of MB and organelle structure, and displays hyperacetylation of key proteins and altered expression of upstream regulators of cell metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 55 publications
2
39
1
Order By: Relevance
“…In youths and adults with T2DM, insulin resistance is associated with muscle mitochondrial dysfunction . In addition, a recent study demonstrated that in adipose tissue from obese children, there was dysregulation of mitochondrial function and biogenesis modulators relative to lean subjects . As MOTS‐c is a key novel endocrine signaling molecule that originates from mitochondria, mitochondrial DNA dysfunction could result in a direct decline in mitochondrial function and progressive loss of MDP expression, which will diminish their functionality as regulatory peptides .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In youths and adults with T2DM, insulin resistance is associated with muscle mitochondrial dysfunction . In addition, a recent study demonstrated that in adipose tissue from obese children, there was dysregulation of mitochondrial function and biogenesis modulators relative to lean subjects . As MOTS‐c is a key novel endocrine signaling molecule that originates from mitochondria, mitochondrial DNA dysfunction could result in a direct decline in mitochondrial function and progressive loss of MDP expression, which will diminish their functionality as regulatory peptides .…”
Section: Discussionmentioning
confidence: 99%
“…7,[29][30][31][32] In addition, a recent study demonstrated that in adipose tissue from obese children, there was dysregulation of mitochondrial function and biogenesis modulators relative to lean subjects. 8 As MOTS-c is a key novel endocrine signaling molecule that originates from mitochondria, mitochondrial DNA dysfunction could result in a direct decline in mitochondrial function and progressive loss of MDP expression, which will diminish their functionality as regulatory peptides. 9 Thus, it is tempting to speculate that the significantly decreased levels of endogenous MOTS-c in insulin-resistant obese children and adolescents may be a consequence of mitochondrial dysfunction, and that the expression of MOTS-c decreases dramatically when the mitochondrial dysfunction reaches a certain threshold, but the presence of such a mechanism remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mitochondrial dysfunction and damage have been implicated in obesity [12,13] and CVD [14]. In particular, platelet mitochondria are important in maintaining thrombosis and hemostasis [15].…”
Section: Introductionmentioning
confidence: 99%